PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP EFEKTIVITAS KERJA PEGAWAI BINAMARGA DAN PEMATUSAN - Setiawan, Indra; Idayanti, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out how far the application of Good Governance principles and its problems to the Performance Effectiveness of the employees of Surabaya city government. The research is qualitative research which is done by analyzing the primary data. Meanwhile, the research method has been done by using co-relational research which is to test the co-relational relationship between the application of good governance principle variables (X) and the dependent variable is effectiveness of employeesâ performance (Y). The samples are 182 people which consist of 22 people in administration, 34 people in planning and beneficial department, 14 people in testing department, supervise and control, 21 people in road and bridge department, 80 people in drainage, and 11 people in Local Technical Implementation Unit (UPTD). The data collection technique has been done by using interview and questionnaire. The interval measurement is used as the research analysis. It can be concluded from the result of the research that the application of good governance principles is in the category of major interval which is between 40-49 (medium), it indicates that the good governance principles has been done by Dinas Pekerjaan Umum Bina Marga dan Pematusan Kota Surabaya is already well. It is supported by the rate of effectiveness of employeesâ performance which is in the category of major interval is between 50-65 (medium) which indicates that the application of the effectiveness of employeesâ performance has been done by Dinas Pekerjaan Umum Bina Marga dan Pematusan Kota Surabaya has been running well.Keywords: Effectiveness of the employees, Good Governance principles, Good Governance